Drainage wastewater analysis in Matamoros, Tamaulipas - Vargas-Ramos, Catalina (Universidad Autónoma de Tamaulipas, 2008)
To this day, the city of Heroica Matamoros, Tamaulipas does not have a treatment system for the wastewater generated locally. The wastewater and rainwater are discharged into open drainages and later drained to a nearby sea. The importance of analyzing the quality of the water in the drain system Veinte de Noviembre is because it transports 71% of the total volume that is generated. This drain system runs across the city from north to south with an approximate length of 12.1 km. The analysis was performed according to the described methodology of the official Mexican standard NOM-002-ECOL- 1996. As a point of reference on the situation of this body of water across the time, a bibliographic research was conducted by going trough the files of the state department that is in charge of managing the wastewater and also previously studies done by the Technological Institute of Matamoros. According to the parameters to evaluate water quality, it was found that the amount of total suspended solids was two times higher than the permissible limits, and that the fats and oils are less than 1% over than the parameters established by the standard. To take advantage of the maximum use of this water, the installation of a water treatment plant is recommended, so the treated water can be later use in irrigation and public services.